A fé em festa: um estudo sobre a espetacularidade do Auto do Divino em Moju-PA - SILVA, Ronilson Brito da (2023)
The festival of the Holy Spirit in Moju/Pa is a tradition that has existed for over 268 years, a commemoration that dates back to colonial times. Like many other manifestations of Catholicism, the feast of the Divine is crossed by cultural manifestations and spectacular events. The Movimento do Mastro as well as the Auto do Divino, two moments within the festivities to the Saint are the moments that most attract the faithful, but it is punctuated by saying that this investigation has the General Objective to analyze the Auto do Divino of the municipality of Moju as a spectacular phenomenon in the festivity.Thus, this study is based on Miguel Santa Brígida (2015); Alexandra Gouveia (2010), Vera Jurkevics (2005), Valeria Salles (2007), Válber Salles (2015) that explain the spectacularity present in the festivity of the Holy Spirit.Therefore, the methodology used is qualitative research linked to ethnocenology. It is concluded that the Auto do divino is one of the spectacular events that takes place within the festivity that aims to propagate the history and origin of Moju, whether through the finding of the dove or the festivity dedicated to the saint of the city, rescuing and preserving the stories that cross the city, its origins and culture, in addition to propagating the Catholic faith, all this through the spectacular manifestations present in the theater and in the artistic forms that are presented on this day.